A Semiotic Analysis of Biotechnology and Food Safety Images in Time, Newsweek, and U.S. News & World Report - Jenn Norwood Tolbert; Tracy Rutherford (Journal of Applied Communications, 2009)
This study examined the photographs and photo illustrations used in Time, Newsweek, and U.S. News & World Report biotechnology and food safety stories in 2000 and 2001. Semiotic theory provided a conceptual framework for interpreting data collected through a quantitative content analysis. The evaluation of 45 images indicated that the news magazines had relatively balanced coverage of the issues. Five categories of images were determined to be used by the news magazines: food, animals, scientists or food handlers, producers, and foreign. These results are consistent with journalism research in relationship to the use of images to create perceptions and support stereotypes. Based on the results of this study, agricultural communications and journalism programs should emphasize visual media literacy. Understanding how images support stereotypes or influence public perception, rather than providing objective information, can be used to develop communications campaigns advocating a point-of-view.
Keywords: Semiotic Analysis; Biotechnology; food safety; Images; Time; Newsweek; U.S. News; World Report; Communications; magazines; journalism programs